2011
DOI: 10.1007/s12668-011-0009-2
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Thermal Analysis of a Wireless Cortical Implant with Two-Body Packaging

Abstract: This article presents the numerical analysis of temperature elevation in the head due to the operation of a wireless cortical implant. The thermal analyses are done by using a finite-difference time-domain simulation tool and a high-resolution 3-D head phantom with 22 different tissues. The effects of the power dissipation level, size, location, and packaging of the implant on the temperature distribution in the head are investigated by using a generic silicon chip. Furthermore, the distribution of the power c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Previous studies have demonstrated the predictive value of numerical bio-heat transfer models for several active head implants, including active microelectrode arrays (MEA) [18], deep brain stimulators [19], an MEA-based cortical implant [20], and a retinal prosthesis [21]. However, due to the unique features of our SU implant, including its ability to simultaneously record and stimulate, the findings from these previous studies do not generalize to our SU design.…”
mentioning
confidence: 87%
“…Previous studies have demonstrated the predictive value of numerical bio-heat transfer models for several active head implants, including active microelectrode arrays (MEA) [18], deep brain stimulators [19], an MEA-based cortical implant [20], and a retinal prosthesis [21]. However, due to the unique features of our SU implant, including its ability to simultaneously record and stimulate, the findings from these previous studies do not generalize to our SU design.…”
mentioning
confidence: 87%
“…The safety of patients in a long-term is the priority of IMDs. The power dissipation of the implant results in temperature elevation of the human brain which must be continuously kept less than 1℃ to prevent tissue damage [6]. Furthermore, the size and location of the implant are regarded as the critical parameters of temperature elevation in the brain.…”
Section: Power Dissipation and Temperature Controlmentioning
confidence: 99%
“…Furthermore, the size and location of the implant are regarded as the critical parameters of temperature elevation in the brain. According to [6], the peak δ factor is 0.083 ℃ for a typical implant dimension of 4×4×0.5 𝑚𝑚 located at the right lobe of the brain. The δ factor is the slope of the plot of temperature elevation versus power consumption.…”
Section: Power Dissipation and Temperature Controlmentioning
confidence: 99%